2017
DOI: 10.1371/journal.pone.0172110
|View full text |Cite
|
Sign up to set email alerts
|

Factor contribution to fire occurrence, size, and burn probability in a subtropical coniferous forest in East China

Abstract: The contribution of factors including fuel type, fire-weather conditions, topography and human activity to fire regime attributes (e.g. fire occurrence, size distribution and severity) has been intensively discussed. The relative importance of those factors in explaining the burn probability (BP), which is critical in terms of fire risk management, has been insufficiently addressed. Focusing on a subtropical coniferous forest with strong human disturbance in East China, our main objective was to evaluate and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 50 publications
(70 reference statements)
1
26
1
2
Order By: Relevance
“…From Table 4, not all of our previously suspected human factors were good predictors of wildfire ignition, our study revealed that proximity to roads, villages and farmland are strong predictors of wildfire ignition, while urban settlements and access to water show poor predictability, which is consistent with other findings (Catry et al, 2010;Dlamini, 2010;Fusco et al, 2016; J. Ye et al Applied Geography 89 (2017) 150-162 ; s(C) is stand deviaton of C; C S is the studentized C. ; s(C) is stand deviaton of C; C S is the studentized C. Martell, & Martín, 2010;Ye et al, 2017;Zhang, Zhang, & Zhou, 2010).…”
Section: Determinants Of Human Wildfire Ignitionsupporting
confidence: 88%
See 1 more Smart Citation
“…From Table 4, not all of our previously suspected human factors were good predictors of wildfire ignition, our study revealed that proximity to roads, villages and farmland are strong predictors of wildfire ignition, while urban settlements and access to water show poor predictability, which is consistent with other findings (Catry et al, 2010;Dlamini, 2010;Fusco et al, 2016; J. Ye et al Applied Geography 89 (2017) 150-162 ; s(C) is stand deviaton of C; C S is the studentized C. ; s(C) is stand deviaton of C; C S is the studentized C. Martell, & Martín, 2010;Ye et al, 2017;Zhang, Zhang, & Zhou, 2010).…”
Section: Determinants Of Human Wildfire Ignitionsupporting
confidence: 88%
“…Consequently, an improved understanding of wildfire risk should address the patterns of human activity and its relation to fire ignition (Dickson et al, 2006;Narayanaraj & Wimberly, 2012;Prestemon, Pye, Butry, Holmes, & Mercer, 2002). Significant research effort has been undertaken to explore the relationship between wildfire and its causative factors with the goal of building predictive models (Cardille et al, 2001; Chas-Amil, Prestemon, McClean, & Touza, 2015;Maingi & Henry, 2007;Narayanaraj & Wimberly, 2012;Romero-Calcerrada, BarrioParra, Millington, & Novillo, 2010;Román-Cuesta et al, 2003;Salis et al, 2013;Syphard et al, 2007;Watts & Hall, 2016;Ye, Wang, Guo, & Li, 2017), and has concluded that wildfire tends to occur in areas near human infrastructure on the human-wildland interface (Zhang, Lim, & Sharples, 2016), and frequently exhibits nonlinear relationships (Hawbaker et al, 2013). However, previous studies mainly concentrate on overall wildfire risk integrating numerous factors simultaneously, yet the importance of human factors on ignition has not received much attention.…”
Section: Introductionmentioning
confidence: 99%
“…However, if we consider the analysis in the long term, air temperature presents a positive relation with fire sources. Results with a negative relation between fire and air temperature were also found by Chang et al (2013); Guo et al (2015); Ye et al (2017), again indicating the complexity of these analyses.…”
Section: Determinant Factors In Fire Occurrencementioning
confidence: 61%
“…The map of wildfire ignition susceptibility can be further used to generate an ignition probability map by using the Monte Carlo approach (Metropolis 1987;Ye et al 2017). To illustrate this, we used the annual ignition data from 1990 to 2015 of Yunnan Province to fit a distribution and randomly generated the number of annual ignitions for 1000 years.…”
Section: Spatial Patternmentioning
confidence: 99%